Gesture Recognition system using Convoluted Neural Networks and Transfer Learning - Swaminathan, Varun R; Agrrawal, Shubhaam; Santhanakrishnan, C (2022 Second International Conference on Advanced Technologies in Intelligent Control, Environment, Computing & Communication Engineering (ICATIECE), 2022)
Webserver is a web application designed to convert images to text, which may then be said out using the anticipated text generated by the image converter. For this application, images are captured through webcam as hand gesture inputs. In addition, Google Home and Amazon's Alexa may be used in conjunction with this software. The collected movements may be used for specific smart device functions, and the software can also call out the gesture inputs in various operating system voices (OS). Browsers as well as smart devices are able to handle these multiple OS voices. TensorFlow was used to create this HTML and JavaScript application. In order to run this JavaScript model, we need the Node.js runtime environment. Using a Machine Learning (ML) method, there is no need to install drivers or libraries in this application. Once a user has found the webpage, the software is ready for use.